PENGARUH PENGGUNAAN MEDIA PICTURE CARD PADA MATERI SIKLUS HIDUP MAKHLUK HIDUP DALAM MENINGKATKAN KEMAMPUAN KOGNITIF DI KELAS 3 SDN MANDALA I - Nur Azizah; Fram Hardiansyah; Muhammad Misbahudholam AR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effect of using picture card media on the cognitiveabilities of 3rd-grade students at SDN Mandala I on the topic of life cycles of living things. This research used a quantitative experimental method with a One-Group Pretest-Posttest design. The research sample consisted of all 3rd-grade students at SDN Mandala I, totaling 10 students. The research instrument was an objective test with 10 questions.Data were analyzed using the Shapiro-Wilk normality test, validity test, Cronbach'sAlpha reliability test, and paired sample t-test with the help of IBM SPSS 29. Thenormality test results showed that the data were normally distributed (p > 0.05). Thevalidity test showed that the instrument was valid (r-calculated > r-table and p < 0.05).The reliability test showed that the instrument was reliable (Cronbach's Alpha = 0.716).The paired sample t-test results showed a significant difference between pretest andposttest scores after using picture card media. It was concluded that the use of picturecard media had a positive effect on improving students' cognitive abilities regarding lifecycle material of living things.